Educational Reform: An Essential Pathway to Successful Education - Qu, Liaojian (Science Insights Education Frontiers, 2025)
Historically social advancement has always been accompanied by educational development, and reforms in education Historically have never failed to attract the attention of the global community. Educational reform is an intrinsic need of the education system per se, as well as a crucial pathway to higher-quality, more equitable and inclusive education. First off, educational reform prompts the education system to adapt to societal changes and technological advancements. A nation’s reforms in education can upgrade the governance structure and management mechanisms of its educational system, enhancing its capability of reaching scientific and transparent decision-making. In the digital transformation of education, for instance, the introduction of data-driven decision-making mechanisms enables the system to accurately identify problems, adjust strategies, and optimize resource allocation (McLure & Aldridge, 2023).